Computing Shortest Path in a Single Valued Neutrosophic Hesitant Fuzzy Network - Saad, M.; Mahmood, T.; Ullah, Kifayat; Jan, N. (The Nucleus, 2020)
In engineering, computer sciences and many other applied sciences, finding shortest path in a network is one of the famous problems. The aim of this manuscript is to develop a novel algorithm for finding shortest path in a network where nodes and edges have some uncertainty. Firstly, the concept of singlevalued neutrosophic hesitant fuzzy graph (SVNHFG) has been introduced with some related graph theoretic results. Some examples are provided to understand the defined concepts. Then, the new algorithm for solving shortest path problems (SPPs) has been introduced followed by a flowchart for a stepwise description. A numerical example is provided in the environment of SVNHFGs to demonstrate the proposed algorithm. The advantages of proposed method over the existing techniques are also studied.